Coloring and Bleaching Properties of 500–1000 nm‐Thick Electrochromic Tungsten Oxide Films Deposited by Reactive Direct Current Magnetron Sputtering. Issue 5 (23rd December 2021) - Mian, Md. Suruz; Yagi, Riko; Oya, Kei; Nakano, Takeo
Abstract : Amorphous tungsten oxide films are prepared on indium tin oxide/glass substrates using reactive magnetron sputtering and their electrochromic (EC) properties are investigated. To achieve the densely colored films, samples of 500 and 1000 nm thickness are deposited with different pumping speeds and oxygen flow rates at Ar 3 Pa atmosphere. The as‐deposited films are similarly transparent (≈80%), but their EC properties vary depending on the deposition conditions and strongly on film thickness. The 500 nm‐thick samples have a transmittance of 4–8% in the colored state, which recover well in the bleached state. In contrast, the 1000 nm‐thick films have very low transmittance (<1%) in the colored state but are not completely recovered. Among 1000 nm‐thick films, large pumping speed and a large oxygen flow rate condition result in comparatively better recoverability. The cyclic voltammograms of 500 nm films show small and balanced charge transfer, while those of 1000 nm films reveal large and unbalanced charge transfer. These indicate that more ions are intercalated into the 1000 nm samples but are not completely deintercalated. These findings contribute to the development of EC applications for light shielding. Abstract : Reactively sputtered thick a‐WO3 films (500 and 1000 nm) at 3 Pa are transparent, colored well less than 4–8% in average transmittance. The 500 nm samples recover satisfactorily, but the recovery of 1000 nm samples is relatively poor. Cyclic voltammetry characteristics agree with this behavior and suggest that the intercalated Li cations could not be removed completely in thicker 1000 nm samples.